Dithienopyrrolobenzothiadiazole‐carbazole based D‐π‐A‐π‐D p‐type conjugated material. Issue 5 (4th September 2020) - Kadam, Vinay S.; Bhatt, Prachi A.; Machhi, Hiren K.; Soni, Saurabh S.; Zade, Sanjio S.; Patel, Arun L.
Abstract: A new π‐conjugated macromolecule (M1 ) having fused pentacyclic N‐bridged dithienopyrrolobenzothiadiazole core unit with carbazole capping linked by vinyl spacers at both ends was synthesized and characterized by nuclear magnetic resonance ( 1 H and 13 C) and high resolution mass‐spectrometry techniques. Photophysical properties of compound M1 was studied by absorption and emission spectroscopy. Compound M1 showed optical HOMO‐LUMO gap of 2.2 eV. Compound M1 showed a solvatochromic effect in fluorescence spectroscopy. DFT calculation showed that M1 possesses nearly planar geometry. The space charge limited current hole mobility of M1 was found to be 3.85 × 10 −4 cm 2 V −1 S −1 . Abstract : D‐π‐A‐π‐D type dithienopyrrolobenzothiadiazole with carbazole‐vinyl capping has been synthesized and studied for hole mobility.